Blurred lines: Examining the mainstream right’s response to the radical right in Argentina (2015-2023) - Zhao, Xi (Revista Elecciones, 2025)
The rise of radical right parties in Latin America has led to a significant reconfiguration of the political landscape, which poses a challenge for established parties and opens a new field of study regarding their strategic responses to this process. This paper presents a case study of Argentina’s mainstream right-wing party, Propuesta Republicana (PRO), with the aim of examining its programmatic changes in response to the rising electoral relevance of radical right parties in Argentina. The analysis encompasses the socioeconomic and sociocultural dimensions, as well as their relationship with democracy. Based on a corpus of public speeches by its presidential and vice-presidential candidates during the last three presidential campaigns (2015, 2019, and 2023), the study tracks the distribution of thematic frequencies in its campaign agenda and investigates its positions on various issues through a qualitative content analysis. The findings reveal a progressive clarification of their liberal stance on economi issues and conservative stance on sociocultural issues, paralleling the growing electoral relevance of the radical right throughout these electoral cycles. These observations suggest an overall strategy of “assimilation” by Argentina’s mainstream right in the face of the electoral threat from the far right, as the boundary between the mainstream right and the radical right becomes increasingly porous.